2016
DOI: 10.2147/ijn.s102552
|View full text |Cite
|
Sign up to set email alerts
|

In vivo osseointegration of Ti implants with a strontium-containing nanotubular coating

Abstract: Novel biomedical titanium (Ti) implants with high osteogenic ability for fast and good osseointegration under normal as well as osteoporotic conditions are urgently needed. Expanding on our previous in vitro results, we hypothesized that nanotubular, strontium-loaded (NT-Sr) structures on Ti implants would have favorable osteogenic effects and evaluated the in vivo osseointegration of these implants in rats. The structures with nanotubes of different diameters were fabricated by electrochemical anodization at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Micro-computed tomography (micro-CT) evaluation was performed in seven of included studies 29 , 31 , 32 , 34 36 . In quantitative assessment, four studies 31 , 32 , 34 , 38 showed Sr-enhanced implants demonstrated stronger effect on all micro-CT parameters including bone volume per total volume (BV/TV), 3D bone distribution such as trabecular number (Tb.N), thickness (Tb.Th), and/or spacing (Tb.Sp) and/or the connective density (Conn.D) than control implants, while other three studies found no statistically significant changes in some parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-computed tomography (micro-CT) evaluation was performed in seven of included studies 29 , 31 , 32 , 34 36 . In quantitative assessment, four studies 31 , 32 , 34 , 38 showed Sr-enhanced implants demonstrated stronger effect on all micro-CT parameters including bone volume per total volume (BV/TV), 3D bone distribution such as trabecular number (Tb.N), thickness (Tb.Th), and/or spacing (Tb.Sp) and/or the connective density (Conn.D) than control implants, while other three studies found no statistically significant changes in some parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of included studies 28 , 29 , 31 , 32 , 34 38 reported the results of biomechanical test including pull-out test or removal torque testing. All studies revealed a significant increase in implant fixation, with removal torque value, the maximal push-out force and/or the ultimate shear strength markedly raised compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification or functionalization is an efficient way to improve metal surface morphology, its chemical composition, and microstructure, which are important factors for implant biological performance. The studies [ 14 , 15 , 16 ] considered bioactive calcium phosphate (CaP) ceramic, similar in composition to bone tissue, which is applied on the Ti alloys to stimulate enhanced osseointegration and new bone formation. Micro-arc oxidation (MAO) also known as plasma electrolytic oxidation (PEO), is a novel method to prepare an in situ CaP coating with a wide range of physical and chemical properties on surface of valve metals and their alloys.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize this risk, a locally administered release of strontium, for example by coating of surgical implants, would be highly beneficial [ 13 ]. Numerous studies found an increased biocompatibility and upregulation of osteogenesis related genes in vitro [ 14 16 ] and an effectively improved implant osseointegration in vivo , in bone-healthy [ 17 , 18 ] and recently in ovariectomized rats [ 19 ]. The spatial dispersion of the therapeutic agent Sr 2+ in rat bone with time in vivo was recently described by Rohnke et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for preparation of strontium-releasing implant coatings involve hydro-thermal synthesis routes [ 15 17 ], Sr-substituted hydroxyapatite coating [ 21 , 22 ], NaOH treatment followed by strontium acetate treatment [ 14 ], electrolytic deposition techniques [ 23 , 24 ] and non-reactive magnetron sputtering [ 18 , 19 ]. For optimum medical performance of such coatings it is assumed, that ionic strontium needs to be released continuously over a period of several weeks while the pharmaceutical effect threshold is in the range of 0.10 mM and defined by the serum strontium level of postmenopausal osteoporosis patients that were treated with strontium ranelate [ 25 ].…”
Section: Introductionmentioning
confidence: 99%